The Influence of Motivation, Work Discipline, and Work Environment on Job Satisfaction of Employees at the Port Authority and Harbor Office (KSOP) Class I Balikpapan City - Tita Audy Anggreini; Misna Ariani; Imam Arrywibowo (Publikasi Indonesia, 2026)
Abstract. This research was conducted to determine the influence of motivation, work discipline, and the work environment on employee job satisfaction at the Class 1 Harbormaster and Port Authority Office (KSOP) in Balikpapan City. The study used a quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to all employees who served as research respondents using a non-probability sampling technique with a purposive sampling method. The sample size for this study was 100 employees. Data analysis used the Partial Least Squares (PLS) method with the assistance of SmartPLS software. The results showed that motivation has a positive and significant influence on employee job satisfaction. Work discipline also proved to have a positive and significant influence on employee job satisfaction. Furthermore, the work environment showed a positive and significant influence on employee job satisfaction. These results indicate that increased motivation, consistent implementation of work discipline, and the creation of a conducive work environment able to increase employee job satisfaction at the Harbormaster and Class I Port Authority Office of Balikpapan City. The conclusion of this study emphasizes that partially the three independent variables have a positive and significant effect on job satisfaction, with motivation to make the greatest contribution, followed by work discipline and work environment, so that optimal management of these three aspects is the key to increasing employee job satisfaction in the Balikpapan Class I KSOP environment.